REDUCING LUPUS PATIENTS' HOPELESSNESS THROUGH BEAUTY CLASS IN MALANG CITY IN HONOR OF WORLD LUPUS DAY - Cesarius Singgih Wahono; Elvira Sari Dewi; Tri Wahyudi Iman Dantara; Perdana Aditya Rahman; Kusworini Handono; Nurdiana Nurdiana; Hani Susianti; Dian Hasanah; Choirinnisa Meilia Ayu Putri; Nora Ariyanti; Handono Kalim (Caring : Jurnal Pengabdian Masyarakat, 2022)
Lupus is a systemic autoimmune rheumatic disease with mild to severe clinical features and can lead to hopelessness if not treated properly. The purpose of this activity is to give a beauty class and see how it affects the hopelessness of lupus patients in honor of World Lupus Day. Methods: Organizing World Lupus Day activities such as experts seminars on lupus at a glance, being friendly with lupus, and staying beautiful with lupus; a musical drama and dance performance by a lupus support group with the theme “You Are Beautiful”; and a lupus beauty class. The activity was completed in one day in May 2018 by collecting pre-test and post-test data on the incidence of hopelessness in lupus patients using the Beck Hopelessness Scale (BHS). A total of 100 lupus patients participated in the activity, and all of them underwent pre- and post-testing. The Wilcoxon Signed Rank Test with α=0.05 was used to analyze the collected data. Results: All participants expressed delight and satisfaction with their participation in this activity. The mean BHS scores before and after the beauty class were 8.62+2.68 and 6.36+1.59, respectively, with a significant difference (p=0.000). Conclusion: Beauty class is a fun way for lupus patients to feel less hopeless about their illness. Every year, an activity to commemorate World Lupus Day is required, which is beneficial for lupus patients.